2012
DOI: 10.1016/j.juro.2011.10.150
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine and Chemokine Receptor Expression in Kidney Tumors: Molecular Profiling of Histological Subtypes and Association With Metastasis

Abstract: Purpose Molecular characterization of renal cell carcinoma (RCC) may help in differentiating benign oncocytomas from malignant RCC subtypes and predict metastasis. Chemokines (e.g., interleukin-8 (IL-8)) and chemokine receptors (e.g., CXCR4, CXCR7) promote inflammation and metastasis. Stroma derived factor (SDF-1) is a ligand for CXCR4 and CXCR7, with six known isoforms. We evaluated the expression of these chemokines and chemokine receptors in kidney specimens. Materials and Methods Using quantitative PCR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
(30 reference statements)
1
30
2
Order By: Relevance
“…In lung cancer, renal tumors and gliomas, CXCR7 expression increases significantly compared to normal tissue, which is associated with the metastasis of these types of cancers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In lung cancer, renal tumors and gliomas, CXCR7 expression increases significantly compared to normal tissue, which is associated with the metastasis of these types of cancers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The frequent overexpression of chemokines and chemokine receptors in various tumor types and their involvement in proliferation, metastasis, and angiogenesis have brought about new avenues targeting the chemokine receptors (10). Tumors from various origins including breast, lung, prostate, brain, and kidney showed in particular overexpression of CXCR7 (11)(12)(13)(14). In some cases, CXCR7 was also shown to induce proliferation (15) and angiogenesis at the primary tumor site due to its expression in tumor cells and associated blood vessels (11).…”
mentioning
confidence: 99%
“…Some studies have shown that CXCR-7 and IL-8 can contribute to tumor proliferation and metastasis in renal cell carcinoma (22). Activation of CXCR7 on tumor blood vessels facilitates the progression of colon cancer with lung metastasis (23).…”
Section: Discussionmentioning
confidence: 99%